The Role of Chinese Herbal Therapy in Methamphetamine Abuse and its Induced Psychiatric Symptoms - Chen, Lin; Ru, Qin; Xiong, Qi; Zhou, Mei; Yue, Kai; Wu, Yuxiang (Frontiers in Pharmacology, 2021)
Repeated intake of methamphetamine (METH) leads to drug addiction, the inability to control intake, and strong drug cravings. It is also likely to cause psychiatric impairments, such as cognitive impairment, depression, and anxiety. Because the specific neurobiological mechanisms involved are complex and have not been fully and systematically elucidated, there is no established pharmacotherapy for METH abuse. Studies have found that a variety of Chinese herbal medicines have significant therapeutic effects on neuropsychiatric symptoms and have the advantage of multitarget comprehensive treatment. We conducted a systematic review, from neurobiological mechanisms to candidate Chinese herbal medicines, hoping to provide new perspectives and ideas for the prevention and treatment of METH abuse.